2017
DOI: 10.1186/s11689-017-9209-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of nonverbal working memory in morphosyntactic processing by children with specific language impairment and autism spectrum disorders

Abstract: BackgroundBoth children with autism spectrum disorders (ASD) and children with specific language impairment (SLI) have been shown to have difficulties with grammatical processing. A comparison of these two populations with neurodevelopmental disorders was undertaken to examine similarities and differences in the mechanisms that may underlie grammatical processing. Research has shown that working memory (WM) is recruited during grammatical processing. The goal of this study was to examine morphosyntactic proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 101 publications
8
23
0
1
Order By: Relevance
“…Findings related to group differences in the relationship between language and planning performance align with prior work showing differences between children with SLI and TD children in the relationship between language and EF performance, even when overall accuracy between groups is not significantly different on EF tasks (Ellis Weismer et al, 2017;Marton, 2008). Prior research on planning focused on measures of inner speech (verbal mediation) and showed that inner speech in children with SLI was less internalized relative to TD peers, which suggests delayed verbal mediation development (Abdul Aziz et al, 2017;Lidstone et al, 2012).…”
Section: Group Differences In Planningsupporting
confidence: 81%
“…Findings related to group differences in the relationship between language and planning performance align with prior work showing differences between children with SLI and TD children in the relationship between language and EF performance, even when overall accuracy between groups is not significantly different on EF tasks (Ellis Weismer et al, 2017;Marton, 2008). Prior research on planning focused on measures of inner speech (verbal mediation) and showed that inner speech in children with SLI was less internalized relative to TD peers, which suggests delayed verbal mediation development (Abdul Aziz et al, 2017;Lidstone et al, 2012).…”
Section: Group Differences In Planningsupporting
confidence: 81%
“…TD monolingual and ASD groups are the focus of this report. Some of these children participated in studies addressing other research questions in prior publications by our research team (e.g., Ellis Weismer et al, 2017;Haebig et al, 2015;Kaushanskaya et al, 2017).…”
Section: Participantsmentioning
confidence: 99%
“…Weismer et al 15 also reported a link between executive function and language in school-age children with DLD. School-age children with language impairment completed both a nonverbal working memory measure and a grammaticality judgment task, and their nonverbal working memory significantly predicted their recognition of grammatical errors.…”
Section: Ellismentioning
confidence: 94%